Chinese volley fire and metanarratives of world history - Noordam, Barend (Journal of world history, 2023)
Volley fire with gunpowder weapons is often seen by modern scholars as one of the important innovations which allowed Europe to politically dominate other cultures and societies. Many historiographical theories, of the kind Lyotard termed metarécits, “metanarratives,” have attempted to explain this phenomenon. Recently, compelling evidence has emerged that other civilizations also practiced the technique, most notably China. This article brings together existing and new evidence that volley fire with firearms was developed and practiced in China long before it appeared in Europe and challenges several of the grand narratives of European exceptionalism. This new evidence shows that the volley fire technique arose in China primarily as a reaction to domestic and foreign (semi-)nomadic cavalry threats, belying geographically deterministic accounts, which suggest that sophisticated infantry tactics with firearms would not arise in states bordering the steppe. This article will also challenge the claim that volley fire in Europe benefitted from its emergence in a competitive system of states undergoing a tradition-challenging Renaissance. I call for a reconsideration of the innovative potential of Eurasian land empires bordering the steppe, and stress the importance of studying political contingencies and cultures of innovation in shaping world history.
Gesehen am 16.01.2026